Light propagation in a system of coupled optical liquid-crystal waveguides - Kabanova, Olga Sergeevna; Melnikova, Elena A. (Journal of the Belarusian State University. Physics, 2018)
Optical liquid crystal (LC) systems with spatial modulation of the refractive index are highly promising as a technological platform for the creation of modern photonic devices of the enhanced functionality. This paper presents a method to create a discrete LC waveguide structure with the electrically controlled depth of the refractive index modulation enabling the spatial control of light fields. Tuning of the optical parameters for the developed waveguide system has been realized on the basis of the electrooptical and nonlinear-optical response of the nematic LC medium. It has been established experimentally that in the case of a low-intensity light beam, polarized as an extraordinary wave, one can implement its guided propagation in the described system of electrically induced LC waveguides. It has been shown that the discrete diffraction mode realized for a high-intensity light beam in the system of coupled optical LC waveguides allows for redistribution of the luminous energy between the specified waveguide channels.
Keywords: nematic liquid crystal; waveguide propagation; optical anisotropy; refractive index modulation